(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Irritable bowel syndrome (IBS) is one of the most common and best studied disorders among the group of functional gastrointestinal disorders. It is a functional bowel disorder in which abdominal pain or discomfort is associated with defecation or a change in bowel habit. Visceral hypersensitivity and increased GIT motility are the main patho-physiological mechanism for developing IBS. IBS present with diarrhoea or constipation or both. Investigations are least needed for diagnosis of IBS rather done to exclude differential diagnosis. Diagnosis of IBS is done on the basis of Rome-III criteria. Proper counseling, dietary management, antispasmotic and antidepressant are the mainstay of treatment. Journal of National Institute of Neurosciences Bangladesh, 2016;2(1): 34-39